Oncolytic Virus Immunotherapy - Marchini, Antonio; Ilkow, Carolina S.; Melcher, Alan (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Dear Readers, Oncolytic Viruses (OV) are self-propagating agents that can selectively induce the lysis of cancer cells while sparing normal tissues. OV-mediated cancer cell death is often immunogenic and triggers robust anticancer immune responses and immunoconversion of tumor microenvironments. This makes oncolytic virotherapy a promising new form of immunotherapy and OVs ideal candidates for combination therapy with other anticancer agents, including other immunotherapeutics. There are more than 40 OVs from nine different families in clinical development and many more at the preclinical stage. Each OV has its own unique characteristics, its pros and cons. Although herpes simplex virus is currently the lead clinical agent, a real champion among the OVs has not yet emerged, justifying the continuous development and optimization of these agents. This book, "Oncolytic Virus Immunotherapy", summarizes the state-of-the-art and gives a comprehensive overview of the OV arena with a particular focus on new trends, directions, challenges, and opportunities.